Symmetry‐Breaking Charge Transfer and Hydrogen Bonding: Toward Asymmetrical Photochemistry. Issue 50 (15th November 2016) - Dereka, Bogdan; Rosspeintner, Arnulf; Krzeszewski, Maciej; Gryko, Daniel T.; Vauthey, Eric
Abstract: Symmetry‐breaking charge transfer upon photoexcitation of a linear A‐π‐D‐π‐A molecule (D and A being electron donating and accepting groups) could be visualized using ultrafast time‐resolved infrared spectroscopy by monitoring the CN stretching modes on the A units. Whereas in apolar solvents, the S1 state remains symmetric and quadrupolar, symmetry breaking occurs within ca. 100 fs in polar solvents as shown by the presence of two CN bands, instead of one in apolar solvents, with a splitting that increases with polarity. In protic solvents, symmetry breaking is significantly amplified by H‐bonding interactions, which are the strongest at the CN group with the highest basicity. In strongly protic solvents, the two CN bands transform in about 20 ps into new bands with a larger splitting, and the lifetime of the S1 state is substantially reduced. This is attributed to the formation of an excited asymmetric tight H‐bond complex. Abstract : Breaking not so bad : The breaking of the symmetry of a quadrupolar molecule upon photoexcitation is visualized using ultrafast transient infrared spectroscopy. Whereas polar solvation leads to an asymmetric distribution of the electronic excitation within 100 fs, H‐bonding interactions amplify the asymmetry and, in the most protic solvents, result in the formation of a totally asymmetric tightly bound H‐bond excited complex.